The politics of youth sexuality : Civil society and school-based education in Croatia - Hodžić, Amir; Budesa, Joan; Irvine, Janice; Štulhofer, Aleksandar (2012)
This article analyzes the development of school-based sex education programs in Croatia to identify the role of civil society organizations (CSOs) in shaping government policy outcomes. We trace the history and recent activities of faith-based and pro-comprehensive education CSOs to identify the political advantages and cultural challenges in advocating systematic sexuality education. Focusing our analysis on the 2004–2008 negotiation process over sexuality and health education programs in Croatian public schools, we aim to make transparent the state reluctance in handling controversial issues, as well as its covert privileging of faith-based initiatives. This decision-making process, we argue, exposes political links between heterosexual values and national culture. It also highlights how sex education policy became a site for reinforcing and challenging heteronormative values, and reveals complex relationships between sexuality, religiosity, and national culture.
Projekt MZOS
ENG